Chinese mining FDI in Africa and compliance with ESG goals - YAN, QING (2022)
The mining industry has always been a field of special concern. With China's opening to the outside world faster and faster, China's foreign direct investment in Africa has increased in recent years, but the mining industry generally contacts the most vulnerable countries and people.Therefore, China's mining investment in Africa has a great negative impact on the local countries. ESG is now a behavioral standard for measuring corporate sustainability. This paper will analyze the ESG aspects of Chinese mining companies to find the reasons why Chinese mining companies are not doing so well and give solutions to improve ESG. This paper reviews the current Outward FDI, Chinese FDI motives, why companies comply with ESG, what ESG means for mining and empirical literature on Chinese mining companies in Africa. To find the differences, I selected three Chinese mining companies, and collect all the secondary information about the company to form a case analysis. Through comparative case analysis, we found the reasons why mining companies are not doing well in terms of environment, society and governance: insufficient supervision, weak legality, and lack of respect for local communities. Lack of community communication and low transparency. Finally, the corresponding solution is given.